1993
DOI: 10.4095/193322
|View full text |Cite
|
Sign up to set email alerts
|

Early silurian brachiopods and biostratigraphy of the Hudson Bay lowlands, Manitoba, Ontario, and Quebec

Abstract: Articulate brachiopods of the Llandovery rocks of the Severn River, Ekwan River and Attawapiskat formations of the Hudson Bay Lowlands comprise 35 genera and 50 species, including 18 new species: Severella pinnigera, Gypidula rudiplicativa, Rhytidorhachis guttuliformis, Rostricellula subtilicostata, Microsphaeridiorhynchus hercostomaticum, Hercotrema spissicostatum, Meifodia discoidalis, Atyrypoidea praelingulata, Atrypopsis severnensis, Parmula hemisphaerica, Merista rhombiformis, Whitfieldella pygmaea, Wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 0 publications
0
29
0
Order By: Relevance
“…(e.g. ) monographed the brachiopods from the Hudson Bay Lowlands area of northeastern Canada, but there are no endemic genera. Jin & Chatterton () comprehensively described the faunas from the Avalanche Lake area of SW district of Mackenzie, NW Canada, where although the detailed correlation within the Llandovery is poorly constrained, there appear to be 11 Aeronian genera, none endemic.…”
Section: Regional Distributionsmentioning
confidence: 99%
“…(e.g. ) monographed the brachiopods from the Hudson Bay Lowlands area of northeastern Canada, but there are no endemic genera. Jin & Chatterton () comprehensively described the faunas from the Avalanche Lake area of SW district of Mackenzie, NW Canada, where although the detailed correlation within the Llandovery is poorly constrained, there appear to be 11 Aeronian genera, none endemic.…”
Section: Regional Distributionsmentioning
confidence: 99%
“…Norford (1971) and demonstrated that the uppermost beds of the Red Head Rapids Formation may be early Llandovery in age, but it has not been proven. Some previous studies documented that this disconformity represents the missing early Llandovery strata (Le Fèvre et al, 1976;Norris, 1993b;Jin et al, 1993). Some previous studies documented that this disconformity represents the missing early Llandovery strata (Le Fèvre et al, 1976;Norris, 1993b;Jin et al, 1993).…”
Section: Introduction Ordovician and Silurian Lithostratigraphymentioning
confidence: 97%
“…Taxonomic, descriptive, systematic, and similar publications involving one or more Royal Tyrrell Museum of Palaeontology (RTMP) authors. Johnston and Goodbody (1988), Hall and Neuman (1989*), Johnston (1991Johnston ( , 1993Johnston ( , 1996, Jin and Lenz (1992), Norford (1992, 1996), Jin et al (1993Jin et al ( , 1995, Chatterton (1996, 1997), Johnston and Collom (1998) • Turtles (excluding marine turtles): Brinkman and Nicholls (1991*, 1993a*, 1993b*), Brinkman and Peng (1993a, Brinkman et al ( , 2000Brinkman et al ( , 2008Brinkman et al ( , 2010Brinkman et al ( , 2012bBrinkman et al ( , 2013b, Peng and Brinkman (1993) Wu et al (1994Wu et al ( , 1996aWu et al ( , 1996cWu et al ( , 1996dWu et al ( *, 2001aWu et al ( *, 2001b.…”
Section: Geology and Chronologymentioning
confidence: 99%